2001
DOI: 10.1080/019262301301418892
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Toxicity of 4-Vinylcyclohexene Diepoxide: A Mechanistic Model

Abstract: Fem ale m ammals are born with a nite number of ovarian primordial follicles that cannot be regenerated; thus, chemicals that destroy oocytes contained in these follicles can produce prem ature ovarian failure (early menopuas e in women). Exposure of women to know n ovotoxican ts, such as contaminants in cigarette smoke, is associated with early menopause . Thus, the potential risks posed by ovotoxic chemicals is of concern. Our studies have focused on the environmental chemical 4-vinylcyclohexene (VCH), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 46 publications
1
70
0
4
Order By: Relevance
“…However, the roles of Rictor/mTORC2 in folliculogenesis are currently unknown. In this study, we demonstrated that Rictor activity and downstream mTORC2 signaling are suppressed in ovaries treated with the ovotoxicant, 4-vinylcyclohexene diepoxide (VCD), an occupational chemical shown to cause POF in human and animal models by accelerating the apoptotic process of atresia (23)(24)(25)(26)(27). Additionally, induction of oocyte-specific ablation of Rictor with the Cre-loxp system using Zp3-Cre and Rictor loxp/loxp mice resulted in POF phenotypes.…”
mentioning
confidence: 88%
“…However, the roles of Rictor/mTORC2 in folliculogenesis are currently unknown. In this study, we demonstrated that Rictor activity and downstream mTORC2 signaling are suppressed in ovaries treated with the ovotoxicant, 4-vinylcyclohexene diepoxide (VCD), an occupational chemical shown to cause POF in human and animal models by accelerating the apoptotic process of atresia (23)(24)(25)(26)(27). Additionally, induction of oocyte-specific ablation of Rictor with the Cre-loxp system using Zp3-Cre and Rictor loxp/loxp mice resulted in POF phenotypes.…”
mentioning
confidence: 88%
“…The epoxide 4-vinylcyclohexene diepoxide (VCD) has ovarian-specific toxicity and follicle-depleting properties (Hoyer et al 2001;Mayer et al 2002). The administration of VCD by injection or ingestion repeatedly over a period of up to 30 days depletes the ovary of follicles leading to ovarian senescence (Mayer et al 2004;Hu et al 2006).…”
Section: Other Contraceptivesmentioning
confidence: 99%
“…There is now an increasing volume of studies which link primordial follicle depletion with xenobiotic exposure, suggesting that these irreplaceable follicles are highly sensitive to www.intechopen.com cytotoxic insult (Hoyer and Devine, 2001;Mattison et al, 1983aMattison et al, , 1983bSobinoff et al, 2010Sobinoff et al, , 2011. It is thought that this sensitivity may stem from the primordial follicles quiescent nature.…”
Section: The Primordial Follicle: Precious and Vulnerablementioning
confidence: 99%
“…The use of ovotoxic xenobiotics as agents of contraception/sterilisation represents a novel approach to fertility control. Of particular interest are xenobiotics which have been shown to cause POF by specifically targeting the primordial follicle population for degradation (Hoyer and Devine, 2001;Sobinoff et al, 2010), thus causing permanent sterility.…”
Section: Ovotoxic Xenobiotics As Agents For Wildlife Fertility Controlmentioning
confidence: 99%
See 1 more Smart Citation